SUMBANGAN PENDALAMAN KITAB SUCI TERHADAP PERKEMBANGAN DAN PENGHAYATAN IMAN UMAT DI STASI SANTA MARIA ASSUMPTA CARUBAN - Putri, Clara Intan Sari; Wilhelmus, Ola Rongan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
Clara Intan Sari Putri “Make a Donation of Scripture Study Activities On the Development and Appreciation of the Faith of Catholics in St. Maria Assumpta Basic Christian Community, Caruban District”. The Holy Scriptures for the Catholics are a source of salvation, because they contain the truth of God's Word. Catholics as the faithful have to read the Scriptures regularly. If they read them regularly then they may naturally explore particular knowledge and values on the Scriptures and at the same time develop their own faith on God. In part of encouraging the Catholics to study and explore the Holy Scriptures, the Catholic Church has dedicated certain months for the Catholics to read and study the Scriptures. This study aimed to explore several aspects regarding the understanding of Catholics about the meaning of the Holy Scriptures, the habit of the Catholics to read the Scriptures, and the effect of reading the Scriptures on the development and appreciation of the Catholics’ faith. In addition, the study also explored the methods used to study the Holy Scriptures. This study used a qualitative method. Data collection was done by personal interview technique. The number of respondents for the study amounted to 5 members of St. Maria Assumpta Basic Christian Community, Caruban District. The respondents were representatives of the community, and activelly involved in the Bible study. The results of study showed that majority of respondents understood enough about the meaning and the values of the Holy Scriptures for their daily life. The study indicated that the respondents did not pay yet serious attention on reading and studying the Scriptures. This was happening because of various obstacles, among others due to their daily activities. The results of study showed that majority of respondents tried to read and explore the Scriptures using digital communication media. The respondents have developed particular efforts to overcome obstacles occuring by trying to be consistent of reading the Scriptures, and building more and more intention to read the Scriptures. The results of study showed that activity of exploring the Holy Scriptures has a significant make a donation on the development and appreciation of the Catholics’ faith. By exploring the Holy Scripture, the faith of the respondents has been growing stronger and much better. However, this was only applied to adults, while young Catholics in the community were less interested in studying of the Scriptures. This could be happened partly due to the method of studying the Scriptures in the community was not in accordance with the expectations of the young Catholics.